The Status of Participating in Discussion Making for Staff of Algerian Universities - Rareeballah Mohammad (University of Science and Technology, Yemen, 2013)
Abstract The aim of this study is to define the level of participation in the decision making concerning the teaching staff members of Algerian universities. We have also to know about differences in surveys concerning this decision. The sample of education is composed of (320) teachers, among whom (130) from the university of Algiers, and (69) from the university of Oran, and (121) from the university of Constantine, from the original population which reaches (1476) member. In order to achieve the aims of the present study, a questionnaire is used to gather information necessary to know the level of participation in the decision making among teaching staff members. This study has shown that the level of participation in the decision making among Algerian universities has reached (80%).in addition, it has been proved that There are no statistically significant differences among the three Algerian universities (Algeria, Oran, Constantine) and which is attributed to the participation in decision - making variable for the teaching staff members.      y and examine its hypotheses. The study reached to a group of findings, most importantly is a strong positive correlation between the role the leadership in the application of total quality management in the University of Science and Technology Hospital and the application's level of TQM in it. The study provided several recommendations based on those findings